2006
DOI: 10.1038/sj.bjc.6603509
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of the selective oral cyclin-dependent kinase inhibitor seliciclib (CYC202; R-Roscovitine), administered twice daily for 7 days every 21 days

Abstract: Seliciclib (CYC202; R-roscovitine) is the first selective, orally bioavailable inhibitor of cyclin-dependent kinases 1, 2, 7 and 9 to enter clinical trial. Preclinical studies showed antitumour activity in a broad range of human tumour xenografts. A phase I trial was performed with a 7-day b.i.d. p.o. schedule. Twenty-one patients (median age 62 years, range: 39 -73 years) were treated with doses of 100, 200 and 800 b.i.d. Dose-limiting toxicities were seen at 800 mg b.i.d.; grade 3 fatigue, grade 3 skin rash,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
174
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(181 citation statements)
references
References 28 publications
4
174
1
1
Order By: Relevance
“…cases, in combination with nongenotoxic agents. 30 A model based on our study is presented in Figure 8. In this study, we have shown that R-Roscovitine inhibits TNFa-induced NF-kB pathway through inhibition of the IKK kinase activity and phosphorylation and degradation of IkBa.…”
Section: R-roscovitine Inhibitsmentioning
confidence: 99%
“…cases, in combination with nongenotoxic agents. 30 A model based on our study is presented in Figure 8. In this study, we have shown that R-Roscovitine inhibits TNFa-induced NF-kB pathway through inhibition of the IKK kinase activity and phosphorylation and degradation of IkBa.…”
Section: R-roscovitine Inhibitsmentioning
confidence: 99%
“…The absence of myelosuppression, reported in preclinical and clinical studies of roscovitine [134,137], is clinically beneficial. However, low hematotoxicity of roscovitine might in reality reflect poor distribution of roscovitine to the bone marrow.…”
Section: 5mentioning
confidence: 99%
“…Alzheimer's disease, viral infections, protozoal infections, and inflammatory diseases, are ongoing. The poor pharmacokinetic profile (rapid metabolism and short elimination half-life in rodents and man) and the insufficient exposure to the drug in cancer patients may explain the modest success in clinical trials [124,131,[135][136][137]. Several attempts to overcome pharmacokinetic barriers that limit the clinical use of roscovitine are ongoing.…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…Combination studies currently recruiting patients are initiated for P276-00 administered along with radiation in head and neck squamous cell carcinoma patients, and in combination with gemcitabine in patients with advanced pancreatic cancer. A phase I clinical trial of R-roscovitine has been performed in 22 patients with advanced cancer utilizing several schedules resulting in only minor therapeutical success with hypokalemia, rash and fatigue as dose limiting side-effects (Benson et al, 2007). Further evaluation of R-roscovitine in patients with non-small cell lung cancer was described: Rroscovitine in combination with cisplatin and gemcitabine in phase I showed similar adverse events, e. g., hypokalemia, liver -glutamyltranspeptidase elevation, vomiting, and a 42.9% response rate in 14 patients (Siegel-Lakhai et al, 2005).…”
Section: Cdk Inhibitors For Cancer Therapymentioning
confidence: 99%